An “Echo in the Soul”: Worship Music in Evangelical Spanish-Language Latino Churches of Oregon - Berhó, Deborah L. (Ecclesial practices, 2020)
Abstract While a majority of the fast-growing U.S. Latino population is Roman Catholic, a significant and growing percentage is Protestant – some calculate that they now number 10 million in the U.S. Despite this significant growth, Latino Protestant churches remain understudied, particularly the music in worship services. Several Latino theologians criticize the music as being of foreign extraction, a form of neocolonialism in the church, not an autochthonous expression of worship. However, these claims do not align with music actually being used in these congregations. This carefully documented study of 25 Spanish language Protestant churches in Oregon reveals that, while music used in worship at one time may have been created and imposed by non-Latinos, this is no longer the case, and bi-musicality is the norm, reflecting the diaspora and agency of the Latino Protestant church.